2014
DOI: 10.1177/0011000014555200
|View full text |Cite
|
Sign up to set email alerts
|

Training in Mental Health Recovery and Social Justice in the Public Sector

Abstract: Individuals who experience serious mental illness (SMI) frequently encounter stigma and disenfranchisement. Attention to this concern necessitates a social justice focus within the mental health field. This article explores the significance and critical foundations of a psychology training experience grounded in a social justice and recovery-oriented perspective to answer the call for a focus on social justice and empowerment for individuals with SMI in mental health recovery. A specific training program is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Counseling psychologists may be particularly adept at organizing and advocating for creative venues that connect veterans with one another and make it possible to have difficult conversations about war in safe and accepting environments. Such advocacy is consistent with the field's emphasis on social action and community engagement (Carr, Bhagwat, Miller, & Ponce, 2014;Danish et al, 2007;Hodge, Danish, & Martin, 2013;Hoffman & Kruczek, 2011;Vera & Speight, 2003). Here, there is an obligation not only to connect veterans with other veterans, but also to create the opportunity for civilians and veterans to engage one another in meaningful, nonjudgmental discussions about the significance of war and the impact of war's violence.…”
Section: Discussionmentioning
confidence: 83%
“…Counseling psychologists may be particularly adept at organizing and advocating for creative venues that connect veterans with one another and make it possible to have difficult conversations about war in safe and accepting environments. Such advocacy is consistent with the field's emphasis on social action and community engagement (Carr, Bhagwat, Miller, & Ponce, 2014;Danish et al, 2007;Hodge, Danish, & Martin, 2013;Hoffman & Kruczek, 2011;Vera & Speight, 2003). Here, there is an obligation not only to connect veterans with other veterans, but also to create the opportunity for civilians and veterans to engage one another in meaningful, nonjudgmental discussions about the significance of war and the impact of war's violence.…”
Section: Discussionmentioning
confidence: 83%
“…The emergence of recovery model care, which focuses on empowering clients to direct their own care with a focus on their individual goals, was developed in part to mitigate stigma and enhance social justice by recognizing the oppression faced by this group (Carr, Bhagwat, Miller, & Ponce, 2014). This model of care also recognizes lived experience of a mental health challenge as a potential asset and frames recovery as an achievement and source of pride, to the extent that the model advocates professional peer support from individuals with lived experience of a mental health challenge as essential in recovery (Carr et al, 2014). There is evidence that this approach is successful in reducing stigma; empirical evidence shows that clients who are provided with higher levels of recovery model treatment resources report lower levels of internalized stigma (Wciórka, Switaj, & Anczewska, 2015).…”
mentioning
confidence: 99%
“…Examining postdoctoral residency training is important because psychologists have increasingly recognized that specialized training is needed to provide adequate treatment for SMI (Carr, Bhagwat, Miller, & Ponce, 2014; Corrigan, Steiner, McCracken, Blaser, & Barr, 2001; Hargrove, 1990; Lefley, 1990; Mueser, Silverstein, & Farkas, 2013). However, many psychologists feel inadequately prepared to do so (Buck, Romeo, Olbert, & Penn, 2014; Mueser, 2012), emphasizing the need not only for specialized didactic and experiential training, but ongoing mentorship as well (Drake, Mueser, & Brunette, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One epidemiological study reported that only 15% of all individuals with SMI were receiving minimally adequate treatment (Wang, Demler, & Kessler, 2002). As such, it has increasingly been recognized that psychology trainees and psychologists require specialized training to provide adequate treatment for those with SMI (Carr, Bhagwat, Miller, & Ponce, 2014; Chu et al, 2012; Cohen, Abraham, Burk, & Stein, 2012; Corrigan, Steiner, McCracken, Blaser, & Barr, 2001; Hargrove, 1990; Hoge, Stayner, & Davidson, 2000; Lefley, 1990; Miller, Carr, Utter, Styron, & Steiner, 2017; Mueser, Silverstein, & Farkas, 2013; Roe, Yanos, & Lysaker, 2006). To bridge this gap, in 2014 the APA released a free curriculum for psychologists and other mental health professionals working with individuals with SMI (APA & Jansen, 2014).…”
Section: The Need For Specialized Postdoctoral Psychology Training In...mentioning
confidence: 99%